Factors affecting stunted growth in children aged 6-24 months in Bawean Island, Indonesia - Arini Haq; Luthfiana Eka Sari; Pitra Sekarhandini; Brigitta Ida Resita Vebrianti Corebima (Pediatric Sciences Journal, 2022)
Background: Stunted is defined as a condition where body length and height are less than -2 SD of the WHO height-for-age z score. The number of stunted children worldwide reaches 129 million or 23.8% of the population. This study aims to scrutinize the factors affecting stunted growth in children aged 6-24 months old in Sangkapura district, Bawean. Methods: This cross-sectional quantitative study in Bawean island, involving children aged 6-24 months old who came to posyandu for height measurement. The purposive sampling technique was used in the study, in which the samples filled a questionnaire consisting of several questions. The data analyses presented are univariate analysis, Chi-Square, and Binary Regression Analysis. Results: The analysis results showed that the factors affecting stunted growth in toddlers are birth weight (<2500 grams), gestational age (<37 weeks), exclusive breastfeeding, and weaning foods. If the baby’s birth weight is less than 2500 grams, is born before week 37 of pregnancy, does not get exclusive breastfeeding, and is given homemade weaning foods, the possibility of the baby being stunted is 91.5%. Conclusion: Several factors affect stunted growth in children aged 6-24 months old in Bawean island. Children who experience all of the factors mentioned above have a 91.5% possibility of being stunted. Among the other factors, babies not exclusively breastfed are 190,019 times more likely to be stunted.